Qualitative Study on the Evaluation of the Supplementary Feeding Program (PMT) for Pregnant Women and Mothers of Toddlers at Mokoau Public Health Center, Kendari City. - Hartati Bahar (Journal of Epidemiology and Health Science, 2025)
Background: Indonesia continues to face significant challenges in achieving the Sustainable Development Goals (SDGs), particularly Goal 2 related to eliminating all forms of malnutrition. Stunting remains a major nutritional problem, prompting the government to implement various interventions, including the Supplementary Feeding Program (PMT) for pregnant women and children under five. This program is expected to improve the nutritional status of vulnerable groups and prevent stunting. Objective: This study aims to evaluate the implementation of the PMT Program at Mokoau Public Health Center by examining the program’s input, process, and output components. Methods: This qualitative study employed in-depth interviews, observations, and document reviews as data collection techniques. A total of six informants participated, consisting of nutrition officers, posyandu cadres, pregnant women, and mothers of children under five at Nanga-Nanga Posyandu. Data were analyzed using content analysis through data reduction, data display, and conclusion drawing. Results: The PMT Program at Mokoau Health Center operates through coordination between health officers and posyandu cadres. Target groups are determined based on data from the Health Office, routine weighing results, and regular posyandu examinations. Nutrition officers ensure the quality and eligibility of the food provided, while cadres assist with distribution. Key challenges include limited cadre availability for home delivery and the absence of recipients during distribution. Despite these obstacles, community response remains positive, and beneficiaries feel the program contributes to improved nutritional adequacy and supports stunting prevention efforts. Conclusion: The PMT Program at Mokoau Health Center is beneficial in improving the nutritional intake of pregnant women and young children and holds potential to support stunting prevention. However, stronger socialization efforts and more equitable distribution mechanisms are needed to enhance program effectiveness.